Shut your eyes tight a novel - John Verdon (Crown Publishers, 2011)
Superstar detective Dave Gurney's renewed efforts to retire are halted by the brutal murder of a young bride at her wedding reception, a crime subsequently linked to a brilliant criminal who targets Gurney's family to further his agendas.